2020
DOI: 10.1042/cs20200904
|View full text |Cite|
|
Sign up to set email alerts
|

Unpuzzling COVID-19: tissue-related signaling pathways associated with SARS-CoV-2 infection and transmission

Abstract: The highly infective coronavirus disease 19 (COVID-19) is caused by a novel strain of coronaviruses – the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) – discovered in December 2019 in the city of Wuhan (Hubei Province, China). Remarkably, COVID-19 has rapidly spread across all continents and turned into a public health emergency, which was ultimately declared as a pandemic by the World Health Organization (WHO) in early 2020. SARS-CoV-2 presents similar aspects to other members of the coronavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 255 publications
0
82
0
3
Order By: Relevance
“…For this reason, the RAS system appears to have a central role in SARS-CoV-2 infection and canonical ACE2 pathway links multiple organ damage in COVID-19. Since SARS-CoV-2 induces ACE2 depletion, it leads to a more extensive conversion of Ang-I into Ang-II via ACE, which then binds to ATR1 receptors ( Battagello et al, 2020 ). When ATR1 is stimulated, this latter in turn stimulates HDAC to up-regulate ACE2 expression and synthesis facilitating SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the RAS system appears to have a central role in SARS-CoV-2 infection and canonical ACE2 pathway links multiple organ damage in COVID-19. Since SARS-CoV-2 induces ACE2 depletion, it leads to a more extensive conversion of Ang-I into Ang-II via ACE, which then binds to ATR1 receptors ( Battagello et al, 2020 ). When ATR1 is stimulated, this latter in turn stimulates HDAC to up-regulate ACE2 expression and synthesis facilitating SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this pathway, renin generated in the kidneys cleaves angiotensinogen from the liver, producing Ang I and then is cleaved by ACE into Ang-II (the substrate of ACE2). Ang I binds to the AT1R and AT2R as well as the RAS system has an important function in SARS-CoV-2 infection ( Battagello et al, 2020 ).…”
Section: Role Of Renin-angiotensin System In the Neuronal Manifestatimentioning
confidence: 99%
“…As previously mentioned, SARS-CoV-2 enters the CNS via the ACE2 or TMPRSS2 receptors ( El Tabaa and El Tabaa, 2020 ; Nemoto et al, 2020 ). In order to decline SARS-CoV-2 entry to neural cells, ACE2 activity should be declined ( Battagello et al, 2020 ). Spike (S) glycoprotein as the main SARS-CoV-2 structural protein with a critical role in binding to the host cell and protecting the virus against some of the host species antibodies, is another target of phytochemicals ( Schoeman and Fielding, 2019 ).…”
Section: Potential Of Phytochemicals Against Covid-19 Neurological Asmentioning
confidence: 99%
“…For example, Battagello et al [ 93 ] summarized data on the significance of cellular stress signals during penetration and into the cell and replication of SARS-CoV-2 and concluded that the appearance of clinical symptoms in individual patients depended on the predominant lesion and invasion of the virus into cells, where ACE2 is considered the main receptor for the protein spike (S-protein), through which the virus can attach to the target cells [ 93 ].…”
Section: A Year Of Fighting the Covid-19 Pandemic: Is It Already Tmentioning
confidence: 99%